Acral verruca‐like presentation of chronic graft‐vs.‐host disease. (5th November 2015) - Park, Joyce H.; Lester, Laura; Kim, Jinah; Kwong, Bernice Y.
Abstract : Background: Chronic graft‐vs.‐host disease (GVHD) is a severe and potentially fatal complication in patients after undergoing allogeneic stem cell transplant. This disease may be hard to diagnose as it has numerous cutaneous presentations. Methods: We report four cases of patients seen at Stanford Hospital between January 2013 to December 2014 with hematologic malignancy who developed hyperkeratotic papules and plaques on the palms and soles after allogeneic hematopoietic stem cell transplant. Results: In all four cases, standard treatments for verruca vulgaris failed. Histopathology uniformly showed basal vacuolar alteration at the dermal–epidermal junction and necrotic keratinocytes around the eccrine glands, consistent with GVHD. Interestingly, all four patients responded to topical immunosuppression. Conclusions: Acral verrucous lesions represent an underrecognized presentation of chronic GVHD. We describe four patients with verruca‐like lesions on the palms and soles following allogeneic HSCT. Histopathology confirmed GVHD, and lesions improved with immunosuppression. It is important for dermatologists and dermatopathologists to recognize this rare presentation of cutaneous GVHD.